EFEKTIVITAS PEMBUATAN GULA SEMUT MENGGUNAKAN METODE KONVENSIONAL DAN MODERN - Daud Irundu; Miftaqul Khoiriyah; Ritabulan Ritabulan (Universitas Andi Djemma Palopo, 2022)
The main raw material in the produce of palm sugar comes from boiling sap water which is taken from flower bunches from the extraction process and collected through the tapping process. In this industry, processing can be done in two ways, namely conventionally and modernly (using machines), the stages that are passed through these two methods are almost the same, the only difference being the tools used. This study aims to determine the palm sugar How to produce using conventional methods and modern, and find out how much effectiveness of making palm sugar with conventional and modern methods . This is a research descriptive quantitative . The results of the research show that the process of making palm sugar consists on four processes that cooking the sap of palm , crystallization , sifting and drying. the different process on the cooking sap and drying palm sugar. Indicators of the effectiveness of making palm sugar in each method are measured from the yield value , water content and production time. Percentage yield the highest generated from production is conventional amounted to 14,51 %. Value levels of water palm sugar that meet the standard ISO generated from production in modern amounted to 2,72 %. Time production by using the methods of modern is more concise than using methods konvensinal with a difference is 130 minutes.